The effect of disinfection of alginate impressions with 35% beetle juice spray on stone model linear dimensional changes - Ramadianto, Anggra Yudha; Hasratiningsih, Zulia; Manurung, Rosida (Universitas Padjadjaran, 2007)
Dimensional stability of alginate impression is very important for treatment in dentistry. This study was to find the effect of the beetle juice spray procedure on alginate impression on gypsum model linear dimensional changes. This experimental study used 25 samples, divided into 5 groups. The first group, as control, were the alginate impressions filled with dental stone immediately after forming. The other four groups were the alginate impressions gel spray each 1,2,3, and 4 times with 35% beetle juice and then filled with dental stone. Dimensional changes were measured in the lower part of the plaster model from buccal-lingual and mesial-distal direction and also measured in the outer distance between the upper part of the stone model by using Mitutoyo digital micrometre and profile projector scaled 0,001 mm. The results of mesial-distal diameter average of the control group and group 2,3,4, and 5 were 9.909 mm, 9.852 mm, 9.845 mm, 9.824 mm, and 9.754 mm. Meanwhile, the results of buccal-lingual diameter average were 9.847 mm, 9.841 mm, 9.826 mm, 9.776 mm, and 9.729 mm. The results of the outer distance between the upper part of the stone model were 31.739 mm, 31.689 mm, 31.682 mm, 31.670 mm, and 31.670 mm. The data of this study was evaluated statistically based on the variant analysis. The conclusion of this study was statistically, there was no significant effect on gypsum model linear dimensional changes obtained from alginate impressions sprayed with 35% beetle juice.